2021
DOI: 10.1002/chem.202005077
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpically and Entropically Favorable Self‐Assembly: Synthesis of C4h‐Symmetric Tetraazatetrathia[8]circulenes by Regioselective Introduction of Pyridine Rings

Abstract: Self‐assembly of π‐conjugated molecules in solution generally occurs owing to either an enthalpic or an entropic gain; however, designing π‐conjugated systems that simultaneously exhibit enthalpically and entropically favorable self‐assembly behavior is challenging. Herein, the self‐assembly behavior of tetraazatetrathia[8]circulenes is disclosed, which is driven by both enthalpy and entropy. Single‐crystal X‐ray diffraction analysis demonstrated that molecules of these tetraazatetrathia[8]circulenes form face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 77 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Cyclic voltammograms and differential pulse voltammograms were obtained under the following conditions; solvent: THF, electrolyte: 0.1 M Bu 4 NPF 6 , working electrode: glassy carbon, counter electrode: Pt, reference electrode: Ag/AgNO 3 , scan rate: 0.1 V/s. Tetraazatetrathia[8]circulene 2 and 1‐butyl‐7‐azaindole were prepared according to the literature [37] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic voltammograms and differential pulse voltammograms were obtained under the following conditions; solvent: THF, electrolyte: 0.1 M Bu 4 NPF 6 , working electrode: glassy carbon, counter electrode: Pt, reference electrode: Ag/AgNO 3 , scan rate: 0.1 V/s. Tetraazatetrathia[8]circulene 2 and 1‐butyl‐7‐azaindole were prepared according to the literature [37] …”
Section: Methodsmentioning
confidence: 99%
“…Tetraazatetrathia [8]circulene 2 and 1butyl-7-azaindole were prepared according to the literature. [37] Synthesis of 3. In a 20 mL Schlenk flask were placed 2 (19.6 mg, 30 μmol), m-chloroperoxybenzoic acid (mCPBA) (118 mg, 16 equiv, containing ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the tetraiodide was coupled with primary amides to give the tetraamides 249.5a – e , which were then subjected to the Vilsmeier–Haack conditions to give the tetraazatetrathia[8]circulenes 249.6a – e . 468 Besides, the silicon- ( 249.8a ) 466 and germanium-containing ( 249.8b ) 469 hetera[8]circulenes could be obtained in two steps from the tetraiodide 249.2 by employing palladium and rhodium catalysis. The X-ray structures of 249.4a , 6a , 8a , b showed that these polycyclic frameworks were essentially planar.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“… Reagents and conditions: (a) 466 NIS, CuI, DMF, 80 °C, 3 h; (b) 467 Pd(PPh 3 ) 2 Cl 2 , CuI, Et 3 N, 60 °C, 3 h; (c) DBU, NMP, reflux, 12 h; (d) 468 CuSO 4 ·5H 2 O, K 2 CO 3 , N , N′ -dimethylethylenediamine, toluene, 80 °C, 20 h; (e) POCl 3 , toluene, 120 °C, 2 h; (f) 466 R 2 SiH 2 , Pd( t -Bu 3 P) 2 , Et 3 N, THF, rt, 48 h; (g) 469 Et 2 GeH 2 , Pd( t -Bu 3 P) 2 , i -Pr 2 NEt, THF, rt, 18 h; (h) 466 [RhCl(cod)] 2 , dppf, toluene, 140 °C, 24 h; (i) 469 [RhCl(cod)] 2 , (C 6 F 5 ) 2 PCH 2 CH 2 P(C 6 F 5 ) 2 , toluene, 140 °C, 20 h. …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%